Efficacy of Constructivist’s Teaching Method in Proving Mensuration Theorem: Implications for Nigeria Senior Secondary School Students - Unodiaku, Stanislus Sochima (Journal of Education and Vocational Research, 2022)
The study was conducted to determine the efficacy of the constructivist’s teaching method (CTM) on teaching proof of mensuration theorem: a panacea for senior secondary school students’ interest and achievement. The population of the subjects was 3095 SSS II students composed of students in secondary schools in the Agbani Education zone of Enugu State. Four research questions and four null hypotheses guided the study. Multi-stage sampling technique was used for the study, based on which 197 students composed of 95 males and 102 females were randomly sampled. Data was collected using Mathematics Achievement Test (MAT) and Mathematics Interest Inventory Test (MIIT). The Cronbach alpha statistic and test-retest methods were used in determining the reliability estimates of the MAT and MIIT respectively which yielded 0.89 and 0.91 respectively. The data obtained with the instruments were analyzed with descriptive statistics (mean and standard deviation) in answering the research questions. The findings of the study clearly showed that CTM is effective in enhancing students’ achievement and interest in mathematics learning, especially in proving mensuration theorems. Those exposed to the treatment performed significantly higher than those exposed to the expository method after the treatment. Moreso, those in the experimental group showed a significant difference in mean interest rating in Mathematics than those in the control group after the treatment (post-test). These recorded significant mean differences in achievement and interest of the students after they were exposed to the treatment showing that CTM is responsible for such enhanced increase in performance of the students and their interest. The observed no significant mean difference in performance and interest between male and female subjects shows that CTM is capable of bridging the existing gap in performance and interest in mathematics between males and females.